The roles of cognitive avoidance, rumination and negative affect in the association between abusive supervision in the workplace and non-clinical paranoia in a sample of workers working in France. (January 2019) - Bortolon, Catherine; Lopes, Bárbara; Capdevielle, Delphine; Macioce, Valéry; Raffard, Stéphane
Highlights: Abusive supervision impacts directly on state paranoia in workers working in France. Cognitive and affective factors act as mediators of abusive supervision on paranoia. Abusive supervision leads to cognitive avoidance that will then provoke rumination. Rumination in its turn increases depression, which will foster state paranoia. Tailored Cognitive and Behavioral Therapy is recommended for supervisory abuse. Abstract: This study examined the relationship between abusive supervision and non-clinical paranoia and explored which cognitive mechanisms are mediating this association (i.e. rumination, cognitive avoidance and negative affect). A sample of two hundred and five French-speaking workers currently in employment in France was recruited to fill in a battery of online questionnaires comprising of the French adaptations of the Abusive Supervision Scale, the State Social Paranoia Scales, the Depression and Anxiety and Stress Scales, the Cognitive Avoidance Questionnaire and the Mini-Cambridge Exeter Repetitive Thought Scale. Mediation analyses showed that the experience of supervisory abuse directly influences state paranoia, however, there were significant mediation effects. Abusive supervision impacted on cognitive avoidance that led to more rumination, which in its turn increased negative affect and this increased state paranoia. Rumination impacted on state paranoia but through the effect of negative affect only. This study showed that abusive supervision works together with cognitive and affective factors to impact on non-clinical paranoia. It is recommended that Cognitive and Behavioural therapy (CBT) is tailored to help workers to cope with experiences of supervisory abuse and associated paranoid thoughts by focusing on replacing rumination and cognitive avoidance strategies for more adaptive cognitive strategies and on how to manage depression.